Climate Services for Anticipatory Action - Presentation at GHACOF64 - Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Tufa Dinku presented at the main program at GHACOF64 held in Addis Ababa, Ethiopia, on May 24, 2023. The presentation covered: 1) IRI’s NextGen seasonal and sub-seasonal forecast system, 2) the Flexible Format Presentation, and 3) Related Challenges.